2019
DOI: 10.1590/s1413-65382519000200005
|View full text |Cite
|
Sign up to set email alerts
|

Estudio Exploratorio sobre Estrategias y Errores de un Estudiante con Trastorno del Espectro Autista al Resolver Problemas de División Partitiva

Abstract: RESUMEN: En los últimos años ha aumentado notablemente el interés por analizar el rendimiento académico de los estudiantes con trastorno del espectro autista (TEA). Entre las materias escolares, las matemáticas son uno de los grandes obstáculos que encuentran estos estudiantes. Por consiguiente, es fundamental mejorar nuestro conocimiento sobre el modo en que los estudiantes con TEA aprenden diferentes conceptos matemáticos para luego proporcionarles métodos de enseñanza adaptados a sus necesidades. Este docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
(25 reference statements)
1
5
0
11
Order By: Relevance
“…This confirms other studies that have shown that children with mathematics disabilities had difficulty comparing Arabic digits (i.e., symbolic number magnitude), but not comparing collections (i.e., non-symbolic number magnitude) (Rousselle & Noël, 2007). More generally, the benefits of using concrete manipulatives during instruction coincide with previous research on teaching arithmetic operations to students with learning difficulties (Baroody & Tiilikainen, 2003), and specifically with ASD (Bruno et al, 2021;Hart & Cleary, 2015;Polo-Blanco et al, 2019;. The use of sequences based on augmentative language to teach strategies to students with this disorder also proved beneficial, as other studies show (Hart & Cleary, 2015;Mirenda, 2003).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This confirms other studies that have shown that children with mathematics disabilities had difficulty comparing Arabic digits (i.e., symbolic number magnitude), but not comparing collections (i.e., non-symbolic number magnitude) (Rousselle & Noël, 2007). More generally, the benefits of using concrete manipulatives during instruction coincide with previous research on teaching arithmetic operations to students with learning difficulties (Baroody & Tiilikainen, 2003), and specifically with ASD (Bruno et al, 2021;Hart & Cleary, 2015;Polo-Blanco et al, 2019;. The use of sequences based on augmentative language to teach strategies to students with this disorder also proved beneficial, as other studies show (Hart & Cleary, 2015;Mirenda, 2003).…”
Section: Discussionsupporting
confidence: 88%
“…The results concerning the student with ASD are especially interesting given the lack of studies that focus on the strategies employed by students with this disorder to solve arithmetic problems (Hart & Cleary, 2015;Polo-Blanco et al, 2019;in press). In this sense, the use of the microgenetic approach was especially useful to observe the type of spontaneous strategies used by the subject with ASD, and how they varied in response to the instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Since the use of these rudimentary strategies can hinder the subsequent learning of arithmetic operations, different researchers propose teaching methodologies so that students with learning difficulties can learn effective solving strategies [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The main difficulties are observed when faced with mathematical word problems that contain indirect language, superfluous information or require several steps to solve (Bae et al, 2015 ). Some studies show that, although ASD students without intellectual disability may use the same strategies as students without ASD diagnosis (from now on, non-ASD) when solving mathematical problems, in ASD students more rudimentary strategies like those based on drawing and counting persist (Alderson-Day, 2014 ; Bae et al, 2015 ; Goñi-Cervera et al, 2022 ; Polo-Blanco et al, 2019 ), while non-ASD children soon exhibit progress to more efficient strategies that require higher level of abstraction, like arithmetic operations (Brissiaud & Sander, 2010 ; Ivars & Fernández, 2016 ; Mulligan & Mitchelmore, 1997 ; Rodríguez Marcos et al, 2008 ; Siegler, 1988 ).…”
mentioning
confidence: 99%
“…Given that the current study focuses on Spanish-speaking children, it should be noted that some of the research works mentioned above (e.g., Ivars & Fernández, 2016 ; Merchán-Naranjo et al, 2016 ; Polo-Blanco et al, 2019 and Rodríguez Marcos et al, 2008 ) have also been carried out with Spanish-speaking students. Regardless of the participants' language, previous studies that focus on ASD children are heterogeneous in terms of the mathematical competencies studied: some focus on creativity and mathematical thinking domains (Hetzroni et al, 2019 ), others explore computational and arithmetic skills (Dubischar-Krivec et al, 2009 ), and geometry and representation of objects (Dixon et al, 2016 ), and a few focus on approaching and solving mathematical problems (Bae et al, 2015 ; Oswald et al, 2016 ).…”
mentioning
confidence: 99%